(untitled) (Revista Brasileira Multidisciplinar, 2024)
There is a need for technology to allow more efficient responses to risks and emergencies, in addition to the growing demand for new technologies to serve the population. This study aimed to search the literature on Unmanned Aircraft Systems (UAS), known as "drones", to identify the main barriers and requirements for the use of Unmanned Aircraft. A Systematic Literature Review (SLR) was performed using four digital libraries, considering articles published from 2011 to 2022 related to Unmanned Aircraft as a tool for search and rescue during emergencies. In total, 1,030 articles were found. Of these, 173 were imported for selection. 86 articles and four other RSL were accepted and thoroughly analyzed. This article discusses different methodologies on how remotely piloted aircraft can be used in applications associated with rescue teams, firefighters, urban management, authorities, hospitals and research institutions. The results aim to allow those involved with related operations to explore promising tools for practical use in critical scenarios, along with their advantages and limitations.